Sistem Pengelolaan Berkas Berbasis Website di Kantor Notaris - PPAT Wahid Nugroho Asri S.H.,M.Kn - Susena, Edy; Puspitasari, Norma; Faricha, Nur (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Notary-PPAT Office Wahid Nugroho Asri, SH,. M.Kn. is the Land Deed Making Official who makes authentic deeds relating to land. In carrying out this work, manual recording is still carried out, that is, it still uses a recording system in an administrative book which consists of a file monitoring management process, and does not provide information about reporting files that have been completed. This results in less time efficiency in searching for file data that is being executed.Based File Management Information System Website at the Notary-PPAT Office. based file management information system website was designed using data collection methods which used several methods, namely observation, interviews, literature study and documentation. Using the waterfall system development method. Using PHP and HTML programming languages. This system uses the help of the Visual Studio Code Editor to visually create and edit PHP, HTML, and CSS documents and manage the pages of a site. PhpMyadmin, MySQL for database storage from XAMPP package, this system uses the CodeIgniter Framework.The result of making a website-based file management system at the Notary-PPAT Wahid Nugroho Asri, SH, Office. M.Kn. can produce a system that is able to simplify the management of files that are being run, and simplify existing business processes.